An Interview with David Onley: On Leadership, Inclusivity, and Re-conceptualization - Pletsch, Carolyn (Disability Studies Quarterly, 2012)
David Onley is the Lieutenant Governor of Ontario. As the first Lieutenant Governor with a visible disability, Onley has committed to using his position to bring attention to issues that affect Ontario's 1.8 million people with disabilities, including, for example, accessibility and obstacles to employment and housing. As such, he has been a significant and effective leader in Ontario's efforts to raise the visibility and to reduce the stigma of disability by speaking regularly and consistently about a positive and more accurate rendering: that disabled workers are assets and contribute significantly to their workplaces, as well as to the larger communities of which they are a part. In this interview Onley reflects on his own workplace experiences, research that would add to the argument for greater inclusivity, and the challenges that lie ahead for those that would make Ontario's workplaces more accessible. Key Words: leadership, inclusivity, workplace accessibility, productivity, re-conceptualization